Post-transcriptional control of plastid mRNA accumulation during adaptation of chloroplasts to different light quality environments. - Deng, X W (1989)
The adaptation of germinating spinach seedlings to yellow and red light was studied and compared with plants grown in white light. Spinach chloroplasts isolated from cotyledons and leaves of yellow and white light-grown plants showed similar membrane structures and compositions, while chloroplasts from plants grown in red light have significant adaptive changes. Based on an equal amount of chlorophyll, these changes include a reduction in the number of photosystem I complexes, an increase of photosystem II antenna size, and an increased ratio of stacked to unstacked membranes in red light-adapted chloroplasts. The decrease in the number of photosystem I complexes per unit of chlorophyll in these chloroplasts was qualitatively correlated with an approximately 10-fold decrease in the level of the psaA mRNA encoding the photosystem I 65-kilodalton to 70-kilodalton chlorophyll apoprotein, as well as with a differential decrease in mRNA levels of other photosynthetic proteins. Light quality adaptations do not significantly affect the plastid to nuclear DNA ratio or the overall chloroplast transcription activity. The relative transcriptional activities of 10 plastid genes, as determined by run-on transcription assays, are similar in chloroplasts from cotyledons and leaves of plants grown under the three light qualities. Only the psaA gene shows a 30% to 40% decrease in transcription activity in chloroplasts of plants adapted to red light. This decrease in psaA transcription activity, however, cannot fully account for the decrease of its mRNA level. We conclude, therefore, that post-transcriptional mechanisms are primarily responsible for the control of differential chloroplast mRNA accumulation in light quality adaptations.